Structural Chemistry of [V2As17]3– and [V2Sb17]4–: A Complex Interplay between V-Pn and Pn-Pn Bonding - Wei-Xing Chen; Anubhav Rajyan; Tao Yang; John E. McGrady; Zhong-Ming Sun (Journal of the American Chemical Society, 2026)
Abstract The ability of the heavier pnictogen elements, P, As, Sb and Bi, to form extensively catenated structures is well established, and a wide range of architectures is known, both for the isolated ions and for their coordination complexes. In this work, we report two new vanadium clusters, [V2As17]3– and [V2Sb17]4–, which contain crown-like VPn8 units, linked by a single bridging atom. Reaction monitoring using ESI-MS suggests a growth pathway involving both VPn8 and VPn9 units, the latter appearing transiently in the reaction mixture. Density functional theory reveals that the redox-active orbital has Pn–Pn antibonding character: the two clusters can therefore be considered to map a segment of the potential energy surface linking the entirely separated fragments to a single fused Pn17 unit.